Understanding Tourist Preferences for Sustainable Tourism Practice in Central Europe - Wicaksono, Tutur; Marhadi (STIE Pariwisata API Yogyakarta, 2024)
This study examines how tourists prioritize sustainable practices in Central Europe using the Kano model. With the growing importance of sustainability in tourism, there is limited research on how tourists evaluate different sustainable practices in this region. The objectives are to classify sustainable tourism practices into five Kano quality categories based on tourist preferences and to identify the key practices tourists prioritize when selecting destinations. A quantitative approach was used, surveying 250 tourists in Budapest, who rated 12 sustainable tourism practices. The data were analysed to categorize these practices as